MISSEL: a method to identify a large number of small species-specific genomic subsequences and its application to viruses classification. Issue 1 (December 2016) - Fiscon, Giulia; Weitschek, Emanuel; Cella, Eleonora; Lo Presti, Alessandra; Giovanetti, Marta; Babakir-Mina, Muhammed; Ciotti, Marco; Ciccozzi, Massimo; Pierangeli, Alessandra; Bertolazzi, Paola; Felici, Giovanni
Abstract Background Continuous improvements in next generation sequencing technologies led to ever-increasing collections of genomic sequences, which have not been easily characterized by biologists, and whose analysis requires huge computational effort. The classification of species emerged as one of the main applications of DNA analysis and has been addressed with several approaches, e.g., multiple alignments-, phylogenetic trees-, statistical- and character-based methods. Results We propose a supervised method based on a genetic algorithm to identify small genomic subsequences that discriminate among different species. The method identifies multiple subsequences of bounded length with the same information power in a given genomic region. The algorithm has been successfully evaluated through its integration into a rule-based classification framework and applied to three different biological data sets: Influenza, Polyoma, and Rhino virus sequences. Conclusions We discover a large number of small subsequences that can be used to identify each virus type with high accuracy and low computational time, and moreover help to characterize different genomic regions. Bounding their length to 20, our method found 1164 characterizing subsequences for all the Influenza virus subtypes, 194 for all the Polyoma viruses, and 11 for Rhino viruses. The abundance of small separating subsequences extracted for each genomic region may be an important support for quick and robust virus identification. Finally, useful biological information can be derived by the relative location and abundance of such subsequences along the different regions.